Twitting the Public Sentiment on the Jakarta Online Zoning System - Ratnawati, Tyas; Iljas, Nuphanudin (Universitas Sebelas Maret, 2021)
In 2018, the zoning system policy began to be rolled out in the New Student Admissions system in Indonesia. Until now, it is still a topic of heated debate. The Jakarta Online Zoning System, for example, is one of the issues. This study investigates and analyzes the Jakarta Online Zoning System policy 2020 using the Noorderhaven theory of eight steps in the decision-making process. The goal is to observe and evaluate in-depth a policy. The data taken came from tweets on Twitter for the period of June-July 2020. Twitter was chosen because the latest topics were always discussed by the public. In addition, Twitter has an advanced search that serves as a means to retrace these topics. Data were analyzed through content analysis. From the results, it was found that the series of policies for the Jakarta Online Zoning System 2020 had applied the eight steps in the decision-making process technique. In addition, the internet has become a virtual community building medium that has great power to evaluate policy performance.